Financial Literacy Deficiency Among Micro Businesses Entrepreneurs From The Perspectives Of Funding Providers - Nurul Aini Muhamed; Fauzias Mat Nor; Syahidawati Hj. Shahwan; Norhaziah Nawai; Junaidah Abu Seman; Mahdhir Abdullah; Mohammad Noorizzuddin Nooh; Aimi Fadzirul Kamarubahrin (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA